Cooling performance and space efficiency improvement based on heat sink arrangement for power conversion electronics. (5th January 2020) - Yoon, Youngchan; Kim, Dong Rip; Lee, Kwan-Soo
Highlights: The overlapped heat sink was investigated for space efficiency and cooling performance improvement. It was confirmed that there was an optimum overlap ratio for maximizing the cooling performance. Fan characteristic curves were generalized for the various operating environment. When the overlapped heat sink is applied, the cooling performance was improved by up to about 35%. Abstract: A heat sink system was miniaturized, and its cooling performance was improved by overlapping the heat sinks. To simulate an axial fan condition (typically used in air-cooled forced convection), a fan characteristic curve was applied to consider the relationship between the airflow rate and pressure drop. On investigating the cooling performance of the overlapped heat sinks, it was confirmed that the heat transfer coefficient was improved owing to the increase in the velocity inside the channel, even though the flow rate was decreased. In addition, the fan curves were generalized to be applied in various fan environments, and correlations were proposed to predict the pressure drop and cooling performance of the overlapped heat sinks. The correlations reflect the heat sink geometry and fan characteristics of the system. The cooling performance was improved by a maximum of 35%, and the volume occupied by the system decreased when the fins overlapped. This suggests the proposed method can maximize the space efficiency and improve the cooling performance in a given environment without changing the geometry of the heat sink.